Relasi Guru Agama Khonghucu dengan Masyarakat di Indonesia - Emma Nurmawati Hadiana; Wakhudin (PT FORMOSA CENDEKIA GLOBAL, 2022)
This article intends to describe the relationship between Khonghucu Religious Education teachers and their students, communication between Khonghucu Religious Education teachers and teachers in general, and their communication with the community. The research uses a qualitative approach with the case study method taking the research subjects of Khonghucu Religious Education teachers in Bali, Banten, West Java, and DKI Jakarta. The results showed that neither party objected to the implementation of the teaching and learning process of Khonghucu Religious Education. The relationship between Khonghucu religious teachers and other teachers and the community is also good. They live in harmony with adherents of other religions. The obstacles faced by Khonghucu Religious Education teachers are more administrative in nature, such as the number of Khonghucu religious adherents not meeting one study group, so that public schools do not organize Khonghucu religious learning.